Does inpatient hyperglycemia predict a worse outcome in COVID‐19 intensive care unit patients?. Issue 3 (18th December 2020) - Saand, Aisha R.; Flores, Monica; Kewan, Tariq; Alqaisi, Sura; Alwakeel, Mahmoud; Griffiths, Lori; Wang, Xiaofeng; Han, Xiaozhen; Burton, Robert; Al‐Jaghbeer, Mohammed J.; Abi Fadel, Francois
Abstract: Background: We undertook this study to evaluate the association between hyperglycemia and outcomes in patients with coronavirus disease 2019 (COVID‐19) admitted to the intensive care unit (ICU). Methods: We conducted a multicenter retrospective study involving all adults with COVID‐19 admitted to the ICU between March and May 2020. Patients were divided into normoglycemic (average blood glucose <140 mg/dL) and hyperglycemic (average blood glucose ≥140 mg/dL) groups. Outcomes such as mortality, need and duration of mechanical ventilation, and length of hospital and ICU stays were measured. Results: Among 495 patients, 58.4% were male with a median age of 68 years (interquartile range [IQR]: 58.00‐77.00), and baseline average blood glucose was 186.6 (SD ± 130.8). Preexisting diabetes was present in 35.8% of the studied cohort. Combined ICU and hospital mortality rates were 23.8%; mortality and mechanical ventilation rates were significantly higher in the hyperglycemic group with 31.4% vs 16.6% ( P = .001) and 50.0% vs 37.2% ( P = .004), respectively. Age above 60 years (hazard ratio [HR] 3.21; 95% CI 1.78, 5.78) and hyperglycemia (HR 1.79; 95% CI 1.14, 2.82) were the only significant predictors of in‐hospital mortality. Increased risk for hyperglycemia was found in patients with steroid use (odds ratio [OR] 1.521; 95% CI 1.054, 2.194), triglycerides ≥150 mg/dL (OR 1.62; 95% CI 1.109, 2.379), and African American race (OR 0.79; 95% CI 0.65, 0.95). Conclusions: Hyperglycemia in patients with COVID‐19 is significantly associated with a prolonged ICU length of stay, higher need of mechanical ventilation, and increased risk of mortality in the critical care setting. Tighter blood glucose control (≤140 mg/dL) might improve outcomes in COVID‐19 critically ill patients; evidence from ongoing clinical trials is needed. Abstract : Highlights Hyperglycemia has been reported in almost half of the patients infected with coronavirus disease 2019. In critically ill patients, hyperglycemia is associated with increased morbidity and mortality, irrespective of preexisting diabetes. In our study, patients with blood glucose ≥140 mg/dL and admitted to the intensive care unit were found to have the worst outcomes in terms of mortality, mechanical ventilation need, and intensive care unit length of stay. Further studies are needed to clarify if outcomes significantly improve with tighter glucose targets. 摘要: 背景: 我们开展了这项研究, 以评估入住重症监护病房(ICU)的新型冠状病毒肺炎(COVID‐19)患者高血糖与预后的关系。 方法: 我们进行了一项多中心回顾性研究, 研究对象为2020年3月至5月间入住ICU的所有患有COVID‐19的成年人。将患者分为正常血糖组(平均血糖<140 mg/dL)和高血糖组(平均血糖≥140 mg/dL)。观察结果包括死亡率, 需要机械通气的时间, 住院和ICU的时间。 结果: 495例患者中, 男性占58.4%, 中位年龄68岁(四分位数范围:58.00~77.00), 基线平均血糖为186.6(SD±130.8)。35.8%的研究队列中存在既往糖尿病。ICU和住院综合死亡率为23.8%, 高血糖组与正常血糖组相比, 死亡率为31.4%比16.6%(P=0.001), 机械通气率为50.0%比37.2%(P=0.004)。60岁以上(危险比HR 3.21; 95% Cl 1.78, 5.78)和高血糖(HR 1.79; 95% Cl 1.14, 2.82)是住院死亡率的唯一有意义的预测因素。使用类固醇(OR 1.521; 95%CI 1.054, 2.194), 三酰甘油≥150 mg/dL(OR 1.62; 95%CI 1.109, 2.379)和非洲裔美国人(OR 0.79; 95%CI为0.65, 0.95)的患者高血糖风险增加。 结论: COVID‐19患者的高血糖与ICU住院时间延长, 更高的机械通气需求以及重症监护环境中死亡风险的增加显著相关。更严格的血糖控制(≤140mg/dL)可能会改善COVID‐19危重患者的预后; 还需要正在进行的临床试验证据进一步证明该结论。